Driving Behavior-Aware Network for 3D Object Tracking in Complex Traffic Scenes - Qingnan Li; Ruimin Hu; Zhongyuan Wang; Zhi Ding (IEEE Access, 2021)
Recently a large number of 3D object tracking methods have been extensively investigated and applied in a variety of applications using convolutional neural networks. Although most of them have made great progress in partial occlusion, the intricate interweaving of moving agents (e.g. pedestrians and vehicles) may lead to inferior performance of 3D object tracking in complex traffic scenes. To boost the performance of 3D object tracking in cases of severe occlusions, we present an end-to-end deep learning framework with a driving behavior-aware model that takes full advantage of spatial-temporal details in consecutive frames and learns the driving behavior from object variations in 2D center point, depth, rotation and translation in parallel. In contrast to prior work, our novelty formulates driving behavior that reasons about the possible motion trajectories of the investigated target for autonomous systems. We show in experiments that our method outperforms state-of-the-art approaches on 3D object tracking in the challenging nuScenes dataset.